Pengaruh Citra Merek Dan Kualitas Pelayanan Terhadap Kepuasan Peserta English Proficiency Test (EPrT) Di Language Development Center (LDC) STT-PLN Jakarta - Yudhy Setyo Purwanto; Amanda Trisia Supriadi (Sekolah Tinggi Teknik - PLN, 2019)
Brand image and service quality in the view of consumers will provide a positive trend in the process of perception experienced by consumers. A good perception will guarantee customer satisfaction. This study aims to determine the extent of the influence of brand image (X1), service quality (X2), both individually and jointly towards customer satisfaction (Y). The research was conducted at the Language Development Center (LDC), a work unit at STT-PLN which organizes the English Proficiency Test (EPrT) for final year students in all majors. The study was conducted for 6 months, from December 2018 to May 2019 where EPrT was held 5 times with 987 participants. Descriptive and inferential analysis was conducted to obtain administrative and questionnaire data. Samples were taken randomly using Slovin formula and produced 100 respondents. The questionnaire was processed by assumption test (validity, reliability, and normality) which then the data was processed by correlation analysis and path analysis to reveal the magnitude of the influence between variables both individually and collectively. The results showed that individually, brand image and service quality provided a positive trend toward customer satisfaction. Brand image has an effect of 25.5%, while service quality is 73.2%. Together, the two independent variables also have a significant influence on the dependent variable, with a ratio of Fcount > Ftable, or 252.40> 3.09.